Corpus Linguistics for Health Communication: A Guide for Research. Gavin Brooks and Luke Curtis Collins. - Yang, Fei (Digital Scholarship in the Humanities)
The article discusses the book "Corpus Linguistics for Health Communication: A Guide for Research" by Gavin Brooks and Luke Curtis Collins. The book provides a comprehensive guide to corpus linguistics methodologies and their application in health communication research, offering insights into the challenges and opportunities in the field. The authors emphasize the need for ethical considerations and the integration of quantitative and qualitative methods in interpreting linguistic data.